Biodegradable Dual Semicircular Patch Antenna Tile for Smart Floors - Khalili, Hossein Fazeli; et al. (IEEE Antennas and Wireless Propagation Letters, 2019)
A dual semicircular microstrip patch antenna implemented on a biodegradable substrate is presented for operation in the [863-873] MHz and [2.4-2.5] GHz frequency bands. To cover these frequency bands, two semicircular patches are compactly integrated onto a biodegradable cork tile, commonly found as support in laminate flooring, serving as a substrate. Thereby, the antenna tile may be seamlessly embedded as a sublayer of the floor structure. A higher-order mode is generated by applying via pins in the antenna topology to produce a conical radiation pattern with a null at broadside and sectoral coverage in the vertical plane. As such, the concealed floor antenna covers all azimuth angles of arrival in smart houses. The antenna performance is fully validated, also when the tile is covered by different polyvinyl chloride sheets. Owing to the supplementary design margins, the antenna impedance bandwidth remains covered. Moreover, the radiation patterns are measured in various elevation planes. Under stand-alone conditions, a radiation efficiency and a maximum gain of 74.3% and 5.8 dBi at 2.45 GHz and 48.1% and 2 dBi at 868 MHz are, respectively, obtained. Its omnidirectional coverage in the horizontal plane, stable performance on the inhomogeneous and biocompatible cork substrate and for various inhomogeneous superstrates, and its low-profile integration make the proposed antenna an excellent candidate for smart floors and smart houses.
Created from Fastlane, Scopus look-up
Keywords: Antenna tile; biodegradable cork; dual-band microstrip antenna; Internet of Things (IoT); smart floors

Towards Realisation of a Non-Invasive Blood Glucose Sensor Using Microstripline - Zeising, Samuel; Kirchner, Jens; Fazeli Khalili, Hossein; Ahmed, Doaa; Lübke, Maximilian; Thalmayer, Angelika; Fischer, Georg (International Instrumentation and Measurement Technology Conference (I2MTC), 2020)

Transcutaneous Energy Transfer System for Cardiac-Assist Devices by Use of Inhomogeneous Biocompatible Core Material - Fazeli Khalili, Hossein; Kirchner, Jens; Bartunik, Max; Werner, Siegfried; Ebel, Nina; Schubert, Dirk W.; Weyand, Michael; Fischer, Georg (IEEE Transactions on Magnetics, 2021)
A novel magnetic liquid silicone rubber composite core design applicable to wireless power transfer (WPT) for medical applications is presented. As a case study, the integration of WPT, including the proposed cores for the coils, with ventricular assist devices (VADs) was investigated. This facilitates transferring 4.6 W of power wirelessly through the skin-layer, which thus allows to disposal of the transcutaneous cable that connects the extracorporal batteries to the implanted blood pump. To enhance the coupling coefficient and consequently increase the WPT efficiency, the geometry of the cores was optimized. This reduces the temperature increase in the implant area. The field and thermal simulations were carried out with CST software. The electrical properties of the proposed design as obtained by simulation were validated by measurements. The simulation results perfectly coincide with the measured results. Finally, a new optimized design with additional high permeability core inserts is introduced to further increase the coupling coefficient. The results indicate that the coupling coefficient is increased from 0.31 to 0.52 with the optimized design compared to the case without cores. Moreover, by fixing the initial temperature as 37 °C, the maximum temperature is decreased from 38.19 °C to 37.27 °C, while keeping the transferred power fixed. Its high magnetic conductivity, biocompatibility, low-loss property, flexibility and Qi-standard compatibility make the proposed WPT design an excellent candidate for the wireless-powering of heart assist devices such as VAD